[18F]AlF-NOTA-ADH-1: A new PET molecular radiotracer for imaging of N-cadherin-positive tumors - Liu, Zhenfeng; Wen, Guanghua; Huang, Yuqiao; Dong, Yanzhao; Wang, Zewei; Alhaskawi, Ahmad; Zhang, Shuyi; Wang, GuoLin; Ye, Qianni; Zhou, Haiying; Lu, Hui; Dong, Mengjie (Frontiers in Oncology, 2023)
The cell adhesion molecule (CAM), N-cadherin has become an important target for tumor therapy. The N-cadherin antagonist, ADH-1 has significant antitumor activity against N-cadherin-expressing cancer. In this study, an [18F]AlF-NOTA-ADH-1 was radiosynthesized, cell binding test was evaluated in vitro, the biodistribution and micro-PET imaging of the probe targeting N-cadherin were also studied in vivo. Radiolabeling of ADH-1 with [18F]AlF was achieved up to 30% not decay-corrected yield with radiochemical purity of >97%. The cell uptake study showed that Cy3-ADH-1 binds to SW480 cells but weakly binds to BXPC3 cells in the same concentration range. The biodistribution results demonstrated a good tumor/muscle ratio (8.70±2.68) of [18F]AlF-NOTA-ADH-1 in PDX tumor xenografts, lower tumor/muscle ratio (1.91±0.69) in SW480 tumor xenografts and lowest tumor/muscle ratio (0.96±0.32) in BXPC3 tumor xenografts at 1 h p.i, which is in agreement with the immunohistochemistry. Micro PET imaging results revealed that [18F]AlF-NOTA-ADH-1 exhibits good tumor uptake in pancreatic cancer PDX xenografts with strong positive N-calcium expression, the lower tumor uptake in positive SW480 xenografts with positive expression of N-cadherin, and significantly the minimal tumor uptake in BXPC3 xenografts with low expression of N-cadherin, which was consistent with the biodistribution and the immunohistochemistry. The N-cadherin-specific binding of [18F]AlF-NOTA-ADH-1 was further verified by significant reduction of tumor uptake in PDX xenografts and SW480 tumor with coinjection of a nonradiolabeled ADH-1 peptide in the blocking inhibition experiment. In conclusion, [18F]AlF-NOTA-ADH-1 was successfully radiosynthesized in a short time, and Cy3-ADH-1 showed favorable N-cadherin-specific targeting ability by in vitro data. The biodistribution and microPET imaging of the probe further showed that [18F]AlF-NOTA-ADH-1 could discern different expressions of N-cadherin in tumors. Collectively, [18F]AlF-NOTA-ADH-1 might be a potential PET imaging probe for non-invasive evaluation of the N-cadherin expression in tumors.